A Case Study of Gorkhali: Private Military and Security Companies in Global Security Assemblages - Koirala, Tek Raj (Unity Journal, 2024)
The news about Nepali citizens joining the Russo-Ukraine war has once again sparked attention among stakeholders regarding Gorkhali’s engagement with global private security companies. The engagement of Gorkhali in the Private Military and Security Companies (PMSCs) is not a new phenomenon; it has been seen since the end of the Cold when it came into existence. As the market of PMSCs rises exponentially, security labourers from countries like Nepal are increasingly joining the same. Gorkhali’s long history of mercenaries and constructed narrative of bravery and loyalty has also attracted PMSCs. Existing literature overlooks the emerging consequence and contradiction of PMSCs-led global security governance to Gorkhali and the complex inter-relationship among PMSCs, client state, Gorkhali, and Nepal. This paper uses the ‘Global Assemblages’ approach to capture multiple actors’ fluid relationships, changes, emerging practices, authority, and institutions. The research looks at consequences and contradictions related to Gorkhali after the 2016 Taliban attack on Nepali security guards and the situation of the same after Afghanistan fell to the Taliban in 2021 while serving for PMSCs. It uses the ‘discourse analysis’ to incorporate books, journal articles, and media interviews of security guards and their families on the research topic. Lastly, research argues that the blurred relation between PMSCs and client states in global security assemblages is not only in the security and military realm but is also seen in the case of taking responsibility for any tragic event/accident of Gorkhali in PMSCs-led global security governance. It is also influencing the local institutions and practices of Nepal.